Nuclear functions of NME proteins - Puts, Gemma S (Lab Invest, 2017)
The NME family of proteins is composed of 10 isoforms, designated NME1-10, which are diverse in their enzymatic activities and patterns of subcellular localization. Each contains a conserved domain associated with a nucleoside diphosphate kinase (NDPK) function, although not all are catalytically active. Several of the NME isoforms (NME1, NME5, NME7, and NME8) also exhibit a 3′–5′ exonuclease activity, suggesting roles in DNA proofreading and repair. NME1 and NME2 have been shown to translocate to the nucleus, although they lack a canonical nuclear localization signal. Binding of NME1 and NME2 to DNA does not appear to be sequence-specific in a strict sense, but instead is directed to single-stranded regions and/or other non-B-form structures. NME1 and NME2 have been identified as potential canonical transcription factors that regulate gene transcription through their DNA-binding activities. Indeed, the NME1 and NME2 isoforms have been shown to regulate gene expression programs in a number of cellular settings, and this regulatory function has been proposed to underlie their well-recognized ability to suppress the metastatic phenotype of cancer cells. Moreover, NME1 and, more recently, NME3, have been implicated in repair of both single- and double-stranded breaks in DNA. This suggests that reduced expression of NME proteins could contribute to the genomic instability that drives cancer progression. Clearly, a better understanding of the nuclear functions of NME1 and possibly other NME isoforms could provide critical insights into mechanisms underlying malignant progression in cancer. Indeed, clinical data indicate that the subcellular localization of NME1 may be an important prognostic marker in some cancers. This review summarizes putative functions of nuclear NME proteins in DNA binding, transcription, and DNA damage repair, and highlights their possible roles in cancer progression.